Antibacterial activity and medicinal properties of ginger (Zingiber officinale) in Bangladesh - Shamantha, Anzinur Nahar (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.